2022
DOI: 10.3390/foods11192957
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic Extraction Process of Polysaccharides from Dendrobium nobile Lindl.: Optimization, Physicochemical Properties and Anti-Inflammatory Activity

Abstract: To optimize the ultrasonic extraction process of polysaccharides from Dendrobium nobile Lindl. (DNP), the extraction method was conducted through a single-factor test and the response-surface methodology (RSM). With the optimal extraction process (liquid–solid ratio of 40 mL/g, ultrasonic time of 30 min, and ultrasonic power of 400 W), the maximum extraction yield was 5.16 ± 0.41%. DNP1 and DNP2 were then fractionated via DEAE-QFF and Sephacryl S-300 HR chromatography. The molecular weight (Mw) of DNP1 was ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…The ultrasonication time is a key parameter affecting the yield of AKUs . The yield of AKUs increased rapidly as the extraction time increased and reached an extreme value of 12.40 ± 0.37% at 30 min (Figure B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ultrasonication time is a key parameter affecting the yield of AKUs . The yield of AKUs increased rapidly as the extraction time increased and reached an extreme value of 12.40 ± 0.37% at 30 min (Figure B).…”
Section: Resultsmentioning
confidence: 99%
“…The ultrasonication time is a key parameter affecting the yield of AKUs. 28 The yield of AKUs increased rapidly as the extraction time increased and reached an extreme value of 12.40 ± 0.37% at 30 min (Figure 1B). When the extraction time was prolonged, the increase in thermal activity accelerated the outflow of polysaccharides from the raw materials, whereas the polysaccharides in the solution were degraded due to the time accumulation effect; thus, the yield of polysaccharides decreased.…”
Section: Effect Of Different Factors On the Efficiency Ofmentioning
confidence: 98%
“…Polysaccharides extracted from plants are natural antioxidant components with unique advantages in skin care (24). Moreover, Dendrobium nobile Lindl polysaccharides (DNP) have been shown to have antioxidant (25), anti‐inflammatory (26), antiapoptotic (27,28) and immunomodulatory (29,30) functions in several disease models or in vitro experiments. Li (31) has recently reported protective effects of DNP against UVA‐induced photoaging in fibroblasts.…”
Section: Introductionmentioning
confidence: 99%
“…It is classified as a superior product in “Shen Nong’s Herbal Classic” because of its excellent tonic properties in alleviating paralysis, lowering Qi, and tonifying the weakness of the internal organs. Previous studies on DNL have mainly focused on its small molecule components, such as phenols, alkaloids, and sesquiterpenes [ 15 , 16 , 17 , 18 ], while only a few studies have investigated its bioactive macromolecules. DNL polysaccharides (DNPs) are among the main active components of DNL, exerting antioxidant [ 19 ], anti-inflammatory [ 17 ], and anti-apoptotic effects [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on DNL have mainly focused on its small molecule components, such as phenols, alkaloids, and sesquiterpenes [ 15 , 16 , 17 , 18 ], while only a few studies have investigated its bioactive macromolecules. DNL polysaccharides (DNPs) are among the main active components of DNL, exerting antioxidant [ 19 ], anti-inflammatory [ 17 ], and anti-apoptotic effects [ 20 , 21 ]. Li [ 22 ] reported that DNPs ameliorate UVA-induced photoaging of fibroblasts.…”
Section: Introductionmentioning
confidence: 99%